2022
DOI: 10.1007/s10439-022-03041-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bilateral Assistance for Hemiparetic Gait Post-Stroke Using a Powered Hip Exoskeleton

Abstract: Hemiparetic gait due to stroke is characterized by an asymmetric gait due to weakness in the paretic lower limb. These inter-limb asymmetries increase the biomechanical demand and reduce walking speed, leading to reduced community mobility and quality of life. With recent progress in the field of wearable technologies, powered exoskeletons have shown great promise as a potential solution for improving gait post-stroke. While previous studies have adopted different exoskeleton control methodologies for restorin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 55 publications
(78 reference statements)
1
18
0
Order By: Relevance
“…Thus, although locomotor patterns can appear highly stereotyped, considerable inter- and intra-individual variability exists. Studies of locomotor behaviors have shown systematic differences in movement patterns based on a wide range of neural (Frisk et al, 2019; Ivanenko et al, 2003; Krogh et al, 2022; Young et al, 2022) and biomechanical perturbations (Genthe et al, 2018; Pan et al, 2022; Reisman et al, 2010; Wang et al, 2022) environmental challenges (D’souza et al, 2020; Larsen et al, 2022), psychological state (Attwood et al, 2021; Elkjær et al, 2022), social status (Steptoe and Zaninotto, 2020; Zaninotto et al, 2013), injury (Garcia et al, 2022; Jang and Wikstrom, 2022; Milner et al, 2022), and disease (Ijmker and Lamoth, 2012; Jonkers et al, 2009; Moura Coelho et al, 2022; Prosser et al, 2022; Russo et al, 2022; Troisi Lopez et al, 2022; Young et al, 2022). Furthermore, locomotor impairments can arise from a wide range of physiological and neurological changes, from the subtle changes that may be indicators of progressive disorders (e.g., aging, cognitive impairments) to profound impairments with brain injury (e.g., stroke, spinal cord injury) that can severely limit locomotor function.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, although locomotor patterns can appear highly stereotyped, considerable inter- and intra-individual variability exists. Studies of locomotor behaviors have shown systematic differences in movement patterns based on a wide range of neural (Frisk et al, 2019; Ivanenko et al, 2003; Krogh et al, 2022; Young et al, 2022) and biomechanical perturbations (Genthe et al, 2018; Pan et al, 2022; Reisman et al, 2010; Wang et al, 2022) environmental challenges (D’souza et al, 2020; Larsen et al, 2022), psychological state (Attwood et al, 2021; Elkjær et al, 2022), social status (Steptoe and Zaninotto, 2020; Zaninotto et al, 2013), injury (Garcia et al, 2022; Jang and Wikstrom, 2022; Milner et al, 2022), and disease (Ijmker and Lamoth, 2012; Jonkers et al, 2009; Moura Coelho et al, 2022; Prosser et al, 2022; Russo et al, 2022; Troisi Lopez et al, 2022; Young et al, 2022). Furthermore, locomotor impairments can arise from a wide range of physiological and neurological changes, from the subtle changes that may be indicators of progressive disorders (e.g., aging, cognitive impairments) to profound impairments with brain injury (e.g., stroke, spinal cord injury) that can severely limit locomotor function.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a significant reduction in the metabolic cost of transport, increase in walking speed and reduction in the soleus activity when increasing PF peak torque were found for individuals with cerebral palsy [17], [18]. Furthermore, we have seen that the effects of the considered control parameters of interest resulted in stronger correlations with a wider range of gait parameters in comparison to other studies which analyzed the effects of varying hip and knee assistance on individuals after stroke [5], [12]- [15] (see Fig. 3…”
Section: Discussionmentioning
confidence: 55%
“…3.B) were considerably lower than the reported minimum adaptation time needed for unimpaired people to get used to powered ankle assistance [27]. This limitation is shared with the existing publications on the same topic for people with stroke (the total time spent walking with the exoskeleton was 20.00 ± 11.66 minutes [5], [11], [14], [15], the number of sessions was 1.17 ± 0.37 [5], [10]- [12], [14], [15], and the time per condition was 2.25 ± 0.83 [5], [11], [14], [15] without including our study; see Fig. 3.B-D) and cerebral palsy (the total time spent walking with the exoskeleton was 16.25 ± 0.00 minutes [17], the number of sessions was 5.66 ± 2.05 [16]- [18] and time per condition was 5.00 ± 0.00 [17]; see Fig.…”
Section: A)mentioning
confidence: 90%
See 2 more Smart Citations